Profile of gene expression of TLR-signaling pathways in colorectal cancer tissues - Bednarczyk, Martyna; Muc-Wierzgoń, Małgorzata; Walkiewicz, Katarzyna; Kokot, Teresa; Fatyga, Edyta; Mazurek, Urszula (International journal of immunopathology and pharmacology, 2017)
Toll-like receptors (TLRs) are involved in transduction of molecular signals in immune process such as induction and regulation of immunity, production of cytokines, and recognition of specific molecular patterns on the surface of microorganisms, but also in cancer development—which was partially proven in previous studies. There is a lack of detailed research on differentiating levels of TLR expression in colorectal cancer at different stages of its advancement, so in our study we want to determine whether there is such a difference of TLRs and TLR-connected protein expression. In this study, 83 samples of colorectal adenocarcinoma (varying clinical degrees) and 40 slices of healthy colon tissue have been analyzed. The delivered material was subjected to homogenization and extraction of total RNA. The isolated RNA was subsequently purified and valued quantitatively and qualitatively. Quantification was performed using a spectrophotometer GeneQuant II. The RNA concentration in the tested samples was determined spectrophotometrically. A qualitative assessment was performed by performing electrophoresis on a 1% agarose gel stained with ethidium bromide. The expression profile of the genes encoding the TLRs was determined using oligonucleotide microarray HG-U133A. To determine the mRNA (messenger RNA), differentiate cancerous tissue from normal colon using PL-Grid Infrastructure. The results were analyzed statistically, taking a significance level P < 0.05. In the study were found three proteins, DUSP2, IFNγ, EIF4A1, associated with TLR system, that differentiate early stages of colorectal cancer of healthy tissue, moreover eleven, inter alia: vascular endothelial growth factor (VEGF), which differentiate high stage of cancer of healthy tissues. The results emphasize the role of pathways associated with TLR activation in the pathogenesis of colorectal cancer. In summary, molecular studies on the development of colorectal cancer will enable the introduction of minimally invasive genetic diagnosis of early forms of cancer. In addition, identification of new signaling pathways can provide the basis for developing new therapeutic methods.